The digital divide profile of Greece: One step further - Georgopoulou, Panagiota (The Greek Review of Social Research, 2011)
The issue of "digital divide" as a new form of social inequality regarding the access to and use of information and communication technologies (ICTs) has not yet received substantial attention in contemporary policy and social debate in Greece. Most of the research has taken place within the framework of the "Observatory for the Greek information society" supported by the EU and established as part of EU-funded initiatives concerning the promotion of the "Information Society" within European countries. Within this context, the aim of this article is to give an overview of the Greek digital divide, drawing on the survey data of the Observatory for Greek Information Society published over the period 2008 to 2010, and at the same time to bring out the fundamental limitations and implicit assumptions underlying such official research. The goal is to uncover the issues at stake and the challenges for further investigation.